Preparation, Evaluation, and Optimization of Atorvastatin Nanosuspension Incorporated Transdermal Patch (Asian Journal of Pharmaceutics (AJP), 2016)
Background: A nanosuspension is a colloidal dispersion of submicron drug particles. Most of the new drugs are poorly soluble in both water and organic solvents. To overcome such solubility problems and bioavailability factors, many traditional approaches have been adopted. One of the most successful and easy method to enhance both solubility and bioavailability of drug was nanosuspension formulation. Aim: The aim was to prepare atorvastatin nanosuspension loaded matrix type transdermal patch using homogenization technique. Materials and Methods: Atorvastatin nanosuspension was prepared by adding 100 mg of drug with 10 mg of surfactant in an aqueous solvent to get a dispersed form, the prepared solution was homogenized at different rpm and then sonicated. Based on the particle size of the formulation, best one of F8 was selected and fabricated into transdermal patch using Hydroxypropylmethycellulose (HPMC), dibutyl phthalate and with different concentration of dimethylsulfoxide (DMSO). Prepared patches were evaluated for various physicochemical parameters such as thickness, weight variation, folding endurance, percentage moisture loss, percentage moisture uptake, tensile strength, and analyzed its release character. Result and Discussion: The obtained transdermal patches were found to be thin, clear, smooth, uniform, and flexible with desired thickness for transdermal delivery of atorvastatin nanoparticles. Formulation FT-3 was selected as an optimized formulation since the release rate was 86.4% at 105 min and tensile strength was 875.6 Â± 104.1. Conclusion: The study concludes that atorvastatin nanosuspension of F8 with particle size of 496 nm and loaded into patch of FT3 of 100 mg HPMC, 0.75 ml DMSO, and 20 % w/w of polymer shown 86.4% Â± 0.82% of drug release at 105 min which evidence that increase in concentration of DMSO increases rate of drug release.